Answer:
(x, y ) = (
,
)
Explanation:
given the 2 equations
+ y = 1 → (1)
= 2y → (2)
multiply (1) by 4 and (2) by 2 to eliminate the fractions
x + 4y = 4 → (1)
x - 3 = 4y → (2)
rearrange (2 ) expressing x in terms of y
x = 4y + 3 → (3)
substitute x = 4y + 3 into (1)
4y + 3 + 4y = 4
8y + 3 = 4 ( subtract 3 from both sides )
8y = 1 ( divide both sides by 8 )
y =
![(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/college/oishxf3znbtm7sgua7hx3bnp2grk4mwmno.png)
substitute this value into (3 ) for x
x = (4 ×
) + 3 =
![(7)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a67aufzacnmx60jrotuctf6zva7tjtyohb.png)
solution is (
,
)